2021
DOI: 10.3390/jcm10102209
|View full text |Cite
|
Sign up to set email alerts
|

Osteoglycin as a Potential Biomarker of Mild Kidney Function Impairment in Type 2 Diabetes Patients

Abstract: Osteoglycin (OGN) could be a biomarker of mild kidney function impairment in type 2 diabetes (T2D). Our study aimed to determine the association between serum OGN and impaired kidney function risk in T2D patients and to analyze its potential role as an estimator of kidney disturbances in this population. This cross-sectional study included 147 T2D patients (65 ± 8 years, 58.5% males), and 75 healthy controls (63 ± 10 years, 36% males). Circulating OGN levels were determined by ELISA. Linear regression modeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Some studies have reported higher osteoglycin levels in serum in T2D patients with nephropathy ( 43 ). Consistently, our previous study reported increased serum osteoglycin levels associated with mild kidney function impairment in patients with T2D compared with healthy subjects proposing osteoglycin as an early biomarker of kidney impairment ( 44 ). In agreement, our results have shown a negative correlation between circulating osteoglycin levels and eGFR in patients with T2D.…”
Section: Discussionsupporting
confidence: 78%
“…Some studies have reported higher osteoglycin levels in serum in T2D patients with nephropathy ( 43 ). Consistently, our previous study reported increased serum osteoglycin levels associated with mild kidney function impairment in patients with T2D compared with healthy subjects proposing osteoglycin as an early biomarker of kidney impairment ( 44 ). In agreement, our results have shown a negative correlation between circulating osteoglycin levels and eGFR in patients with T2D.…”
Section: Discussionsupporting
confidence: 78%
“…glucose, serum creatinine, blood urea, urine albumin / creatinine ratio, total cholesterol, TG and LDL, while there was negative correlation between OIF and both of eGFR and HDL in T2DM patients (Normoal buminuric, microalbuminuric and macroalbuminuric groups). These outcomes support the findings of Wang., et al, [7] who said that, there was an important positive relation between OIF and the same parameters as well, Tamer A., et al, [8] , & González., et al, [10] , showed that, there was a positive correlation between OIF and urinary albumin creatinine ratio, while there was a negative correlation between OIF and eGFR in diabetic patients. Tamer A., et al, [8] , reported that OIF and creatinine exhibited a positive association whereas eGFR and OIF had a negative association.…”
Section: Resultsmentioning
confidence: 96%
“…OIF has important functions in both lipid and glucose metabolism and is integrated into the typical vascular matrix. OIF has therefore been recently hypothesised to play an essential part in the glomerular disease related to nephropathy caused by diabetes, and it has also been investigated as an indicator for earlier DN [5] . The work's aim was to clarify the significance of OIF as a sensitive indicator for the detection of early diabetic nephropathy.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, T2D will affect 693 million people in 2045 ( 2 ). Uncontrolled T2D can lead to severe chronic conditions, including micro and macrovascular diseases ( 3 , 4 ). Thus, causing enormous pressure on healthcare systems.…”
Section: Introductionmentioning
confidence: 99%